The ethically responsible organization - Sims, Ronald R. (Contemporary human resource management., 2022)
Today's businesses have an obligation to conduct themselves in an ethical and responsible manner at all times. Fortunately, many businesses have historically embraced the idea that they can operate in an ethically & responsible manner. However, there are way too many companies that are willing to cut corners and do whatever it takes to make a profit, thus contributing to the vortex of mistrust, distrust, misinformation, disinformation and less than full disclosures as a result of their unethical misconduct. This book takes the position that 'enough is enough' and argues that all businesses can and must be ethically responsible no matter its size or whether it operates locally or globally. The book describes the features of an ethically responsible (e.g., ethical and socially responsible) organization that is committed to always "doing the right things" which means they are committed to building, institutionalizing and sustaining an ethically oriented organizational culture. Ethical responsibility means maintaining --even improving-- your bottom line, while setting a high bar for high ethical standards AND making a positive contribution to society. The book argues that organizations must be attentive to ensuring that the culture has as its core accountability, responsibility, and learning which means it invests in developing and expecting all of its employees to be fully engaged in making ethical decisions and being ethical leaders. The book also discusses what it means to be an ethically responsible global business, leader, middle manager, and lower level employee.The Ethically Responsible Organization provides a detailed look at the importance of organizations doing preventive work to avoid ethical falls or scandals and takes the position that if such a fall or scandal occurs then the company should seize the moment and learn from the experience by becoming a learning organization. The book also takes the position that an ethically responsible organization is already a learning organization where continuous inquiry, diagnosis, reflection, learning and self-correction is the keystone of the way it operates. Finally, the book offers some ideas on how organizations can reinforce and sustain themselves as ethically responsible businesses today and in the future by taking a strategic approach to ethics that includes constant and consistent ethics training and education for all its employees and partners. In the end, the purpose of the book is to continue to increase our understanding of why organizations stray from "doing the right things" and how a focus on being ethically responsible can position companies to avoid or quickly respond to any potential ethical misconduct or find themselves in the list of the years' top ethical scandals. This book is written for all those who also take the stance that 'enough is enough' when it comes to the headlines of another failure because the organization's leaders would not commit to being ethically responsible and find themselves in the throes of an ethical scandal and unable to recover from it - and like "Humpty Dumpty, all the kings horses and all the kings men the company can't recover from what was a preventable ethical fall."